VOLUME 5, NO 2 (2017) - Chief, Editor In (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2017)
Dear readers, Aro-the Scientific Journal of Koya University is closing its ninth issue (Vol V, No 2, 2017) after an exciting yet dynamic season of valuable inputs by our research community and supportive reviewers. Aro is publishing its 4th issue as an internationally listed Scientific Journal in Kurdistan Region of Iraq. Notably, Aro has been accepted for indexing in the Emerging Sources Citation Index (ESCI), a new edition of Web of Science™ as of Feb 2016. Content in this index is under consideration by Thomson Reuters to be accepted in the Science Citation Index Expanded™ (SCIE). Aro’s individual articles are currently listed by Thomson Reuters using articles unique DOI numbers which is a historical achievement for our academic community. Aro is ending its fifth year journey in leading the quality of regional scientific publications with global impact. The editorial team has been working tirelessly to keep the novel mission and sustain Aro’s future publications with greater impacts and citations. It is exciting that Aro has been awarded to DOAJ Seal listing which is an indication of a trusted high standard open access scientific work that so far haven allocated to 88 journals worldwide only. The upcoming new season will be an even more exciting period in Aro’s life as Thomson Reuters will examine our journal for full permanent listing. Despite all ongoing regional conflicts and economic downturn which still having a great impact on scientific research activities and funding of the regional universities in general and Koya University in particular, Aro is continuing to receive great numbers of well-motivated quality papers which shows its steadily growing trust among researchers in the region, demanding the increased volume of publication. Nevertheless, Aro is finding more focus in applied sciences with research values in current regional issues having International impacts. Aro was created with long-term visions of becoming accessible to all researchers in Kurdistan and beyond, and covering a wide range of scholarly disciplines in sciences. Aro is a peer-reviewed, open access journal that publishes original scientific research, global news, letters and commentary as well as review articles in areas of natural sciences and technology. In this issue you will have access to original research papers in variety of areas, such as Physics, Biochemistry, Materials Science and Petroleum, Chemical and other fields of Engineering. The great responses from researchers, academics and professionals in the last five years have made us to create a wider Editorial Board which serves the wider submitted scientific manuscripts. However, it is clear that having a dedicated and well organised editorial board for the journal is only one side of the coin. The other is the ability to attract submissions of quality research and scholarly work. We are thankful to all of those who put their trust in Aro and presented their original research work for publication in Vol V, No 2 (2017) of the journal, as well as, our thanks are extended to the 16 peer-reviewers from the Universities worldwide for their efforts in reviewing and enabling this issue of Aro. Your support and feedback are invited and appreciated. Dilan M. Rostam Editor-in-Chief Wali M Hamad Executive Publisher Dilan M. Rostam, Salah I. Yahya, Basim M. Fadhil, Fahmi F. Muhammad, Mohammed H.S. Zangana, Jorge Correia and Fouad Muhammad Executive Editorial Board